Effect of Plant Growth Regulators on Corm Production and Vase Life in Gladiolus - Padmalatha, T; Reddy, G Satyanarayana; Chandrasekhar, R (Journal of Horticultural Sciences, 2015)
Influence of plant growth regulator sprays on corm production and post-harvest life of two gladiolus cultivars, Darshan and Dhiraj, was investigated for two consecutive years, 2008-09 and 2009-10. Growth regulators, viz., gibberellic acid (100 and 150ppm), tri-iodo benzoic acid (TIBA) (50 and 100ppm), 2-chloro, 4-pyridyl phenyl urea (CPPU) (2.5 and 5ppm) and brassinosteroid (BR) (5 and 10ppm) were sprayed at the 3rd and 6thleaf stage. Cv. Darshan recorded maximum number of large cormels per plant and cormel weight, while, cv. Dhiraj recorded maximum number of small cormels per plant in treatments of pre-harvest foliar sprays with plant growth regulators. Foliar sprays of BR (10ppm) and GA3 (150ppm) significantly increased number of corms produced per plant, corm size, corm weight, and propagation coefficient. Number of large cormels and total number of cormels per plant were significantly higher in BR (10ppm), followed by TIBA (100ppm). BR (10ppm) and TIBA (100ppm) produced maximum number of small cormels per plant. Weight of cormels per plant was maximum in BR (10ppm) and GA3 (150ppm). Post-harvest studies revealed that cv. Darshan recorded maximum diameter of second fully-opened floret and higher vase-life than cv. Dhiraj with pre-harvest foliar spray of plant growth regulators. Pre-harvest foliar spray of GA3 (150ppm), BR (10ppm) and CPPU (5ppm) induced earliest first-floret opening and recorded maximum value for number-of-floretsopen- at-a-time per spike, diameter of second fully-opened floret, and vase-life. Foliar spray of BR (10ppm) and GA3 (150ppm) at 3rd and 6th leaf stage can be recommended for large-scale multiplication of quality planting material and longer vase-life of flower spikes, respectively, in gladiolus.
Keywords: Gladiolus; Corm; Vase-Life; GA3; Brassinosteroids; CPPU